THE IMPORTANCE OF NON-GOVERNMENT NON-COMMERCIAL ORGANIZATIONS IN THE DEVELOPMENT - Nazarov, Nurali (Журнал иностранных языков и лингвистики, 2023)
In the article, the participation of non-governmental non-profit organizations in the processes of physical education and sports development is scientifically analyzed. The importance of non-governmental non-profit organizations representing the interests of various social groups in Uzbekistan in increasing the development, prestige and educational value of sports is highlighted.